Cultivating faculty readiness to reflect: reconstructing Dewey's attitudes for reflection as character strengths. Issue 3 (4th May 2022) - Greenberger, Scott W.; Or, Justina
ABSTRACT: This article presents a reconstruction of John Dewey's attitudes for reflection as character strengths for the purpose of assessing faculty readiness to reflect. As the editor of an academic journal that uses the Guide for Reflective Practice (GRP), I determined the need to assess faculty readiness to write reflectively. In Deweyan terms, readiness involves having certain attitudes that position the reflective practitioner to be effective in reflection. These attitudes are open-minded, wholeheartedness, and responsibility. We reconstruct these attitudes as character strengths, and we show how the specific Deweyan attitudes align with a modern character strengths classification. We then outline steps to use the prominent character strengths assessment tool (VIA-IS) to assess faculty character strengths and provide small-dose strategies to enhance existing character strengths for the purpose of engaging in effective reflection. This inquiry is preliminary. As such, we recommend future empirical research into the efficacy of the VIA-IS and small-dose strategies to assess and enhance faculty readiness for reflection from a Deweyan perspective.